A polyanionic molybdenophosphate anode for a 2.7 V aqueous pseudocapacitor. (November 2019) - Song, Yu; Deng, Pan; Qin, Zengming; Feng, Dongyang; Guo, Di; Sun, Xiaoqi; Liu, Xiao-Xia
Abstract: Aqueous supercapacitors usually suffer from low cell voltage (e.g. < 2 V) which furthermore limits the energy density. Herein, a new polyanionic molybdenophosphate anode that largely extends the cathodic stability of water and allows the assembly of a 2.7 V aqueous supercapacitor is reported. The molybdenophosphate material is deposited on 3D exfoliated graphite substrate via a facile electrochemical method. The electrode is further modified over an electrochemical activation process to introduce more oxygen vacancies and enlarge the lattice, which synergistically improve the charge transfer kinetics. The activated molybdenophosphate film exhibits remarkable pseudocapacitive performance: 556 F g −1 capacitance at 4.5 A g −1, ultralong cycle life of 100 000 cycles with no sign of capacitance decay, and low cutoff working potential of −1.5 V vs. SCE. Further investigations show that the charge storage process is associated with the cations in the electrolyte and the material undergoes multi-electron transfers within the functioning potential range. Coupling with a manganese oxide cathode, a 2.7 V aqueous supercapacitor is assembled and delivers a high energy density of 89.2 Wh kg −1 at the power density of 2733 W kg −1 . The development of polyanion-based pseudocapacitive materials would open up new opportunities for the fabrication of high-performance energy storage systems. Graphical abstract: Image 1 Highlights: A new polyanionic molybdenophosphate anode is demonstrated for pseudocapacitor. The molybdenophosphate anode exhibits excellent capacitive performance. A 2.7 V aqueous supercapacitor is assembled with high energy density.